REFLEKSI TEOLOGIS TENTANG CINTA, HASRAT, DOSA, AMPUNAN, DAN KESELAMATAN DALAM LIRIK LAGU METALLICA "THE UNFORGIVEN": SEBUAH PERSPEKTIF TEOLOGI PUITIK - Dian Nurrachman; Yeni Huriani; Rifki Rosyad (Epigram, 2025)
In today's modern development, poetry has transformed into—and contributed to shaping—songs in popular culture. Song lyrics in popular culture are very similar to traditional poetry, which evolved as a modern expression of a timeless art form. Song lyrics, as an integral part of popular culture, function as a form of storytelling and meaning-making. By retelling human experiences and emotions, they create narratives that resonate deeply with audiences, often reflecting themes of hope, despair, love and redemption. These interactions underscore the idea that theology does not stand alone, but is embedded in the cultural and emotional currents that define human existence. In this context, bands like Metallica stand out as profound contributors. Their ability to channel deep personal experiences and universal human themes into their music not only defines their art but also underscores their connection to the spirit of the culture. Metallica is one of the most influential heavy metal bands of all time, and their lyrics have had a profound impact on the genre. This present research specifically examines the theological reflection of Metallica's song lyrics, which requires an analysis of how Metallica's song lyrics contain elements of theological reflection, especially those related to desire, love, sin, forgiveness, and salvation. Therefore, this present research is more focused on the question of how do Metallica’s song lyrics, especially “The Unforgiven”, reflect theological values in relation to desire, love, sin, forgiveness and salvation. The purpose of this research is to find the theological reflection by taking the object of only song lyrics from “The Unforgiven” which was released in 1991 inside Black Album.